Nutrient intake and adequacy among children 12–18 months of age in the urban slums of Mumbai, India (P11-093-19) - Rajagopalan, Kripa; Huey, Samantha; Venkatramanan, Sudha; Udipi, Shobha; Thakker, Varsha; Thorat, Aparna; Potdar, Ramesh; Haas, Jere D.; Finkelstein, Julia L.; Mehta, Saurabh (Oxford University Press, 2019)
To examine the mean nutrient intake among young children 12–18 months of age in urban slums of Mumbai, b) to determine the adequacy of micronutrient intake in their diet as per the National Institute of Nutrition (NIN) recommendations for optimum growth and development, and c) to determine if there is a difference in the nutrient intake of those randomized vs not randomized to the trial involving feeding of iron- and zinc-biofortified pearl millet complementary foods.